Functionally Graded Piezoelectric Energy Harvester: A Numerical Study - Kumar A.; Ansari M.N.M.; Ibrahim S.M.; Thomas P.; Vaish R. (MDPI, 2023)
The performance of linear energy harvesters is primarily confined to a very narrow operating frequency bandwidth around its natural frequency. Even a slight deviation of the excitation frequency from the fundamental frequency of the system tremendously reduces the harvesters performance. In order to minimize this shortcoming, the presented study considers the piezoelectric energy harvester with magnets introducing non-linearity in the system. The simple harmonic balance method is used to solve the non-linearity and for computing the voltage output and power in the frequency domain. In addition, the study also incorporates the functionally graded piezoelectric materials because of their superior properties. The distance between magnets (d0) has been varied from 0.4 mm to 10 mm along with grading index (n) in the range of 0 to ?. Finally, voltage and power across the resistance were computed. The effective harvesting frequency range for d0 = 0.4 mm and n = 1 is observed in the range of 20 Hz to 85 Hz, while it was only between 35 Hz and 65 Hz for d0 = 10 mm, yielding a 216% increase in the frequency bandwidth. Under different case studies, the peak output power varied from 2 mW (d0 = 0.4 mm and n = ?) to 6 mW (d0 = 10 mm and n = 0). 2022 by the authors.